PERBEDAAN ABNORMAL RETURN DAN VOLUME PERDAGANGAN SAHAM SEBELUM DAN SESUDAH PENGUMUMAN SUSTAINABILITY REPORTING AWARD (SRA) TAHUN 2017 - Alpius Ada; Robert Jao; Beauty Beauty (Fakultas Ekonomi dan Bisnis Universitas Atma Jaya Makassar, 2018)
This study aims to prove empirically the differences of abnormal return and tradingvolume that occurred before and after the announcement of Sustainability ReportingAward (SRA) in 2016. The number of samples used in this study were 9 companiesconsisting of listed companies in Indonesia Stock Exchange which won the SRA 2016award by using sustainability reporting as indicators based on GRI G-4. The data usedare secondary data in the form of daily closing stock price, composite stock price index(IHSG), and daily stock trading volume obtained from www.idx.co.id andwww.finance.yahoo.com with 11 days observation period. Calculation of abnormalreturn using market-adjusted model while for trading volume of stock using tradingvolume activity (TVA). Hypothesis testing is done by using Wilcoxon Sign Rank test.The results showed that there was no difference in abnormal return and stock tradingvolume before and after thevannouncement of Sustaianability Reporting Award (SRA)in 2016.